A Strengthening the Capacity of Village Community Institutions through Village-Owned Enterprises in Sumbermulyo Village Bantul, Yogyakarta - Hendy Setiawan; Nur Wahyu Sulistyo (Institut Pemerintahan Dalam Negeri, 2021)
The success of village-owned enterprises management cannot be separated from the quality of the performance and leadership of a village head. The more village-owned enterprises can develop rapidly, then there is the role and contribution of the Village Head as a catalyst for strengthening village community institutions. The purpose of this article is to provide an analysis related to how to strengthen village community institutions. Related to the focus of this research, namely the case of village-owned enterprises in Sumbermulyo Village, because the Village Head of Sumbermulyo has repeatedly been named the best Lurah in Yogyakarta, so whether this is in line with the development of village-owned enterprises in the village. The method used in this study uses a descriptive qualitative approach. Data collection techniques in this study used interview, observation, and documentation techniques. Processing research data using the stages of data presentation, verification, and drawing conclusions. The results of the study show that the management of the Sumbermulyo village-owned enterprises has not been able to run effectively and still encounters obstacles so that it is still far from being successful. This is related to strengthening the capacity of village governance which is still minimal so that further direction is needed. But on the other hand, independent innovations outside village-owned enterprises have also been found which are much more successful in their management, so that this can also be a means to form and revitalize village-owned enterprises so that their existence can be in line with village progress.